The systematic approach to describing conformational rearrangements in G-quadruplexes - Tsvetkov, Vladimir (J Biomol Struct Dyn, 2016)
Conformational changes in DNA G-quadruplex (GQ)-forming regions affect genome function and, thus, compose an interesting research topic. Computer modelling may yield insight into quadruplex folding and rearrangement, particularly molecular dynamics simulations. Here, we show that specific parameters, which are distinct from those commonly used in DNA conformational analyses, must be introduced for adequate interpretation and, most importantly, convenient visual representation of the quadruplex modelling results. We report a set of parameters that comprehensively and systematically describe GQ geometry in dynamics. The parameters include those related to quartet planarity, quadruplex twist, and quartet stacking; they are used to quantitatively characterise various types of quadruplexes and rearrangements, such as quartet distortion/disruption or deviation/bulging of a single nucleotide from the quartet plane. Our approach to describing conformational changes in quadruplexes using the new parameters is exemplified by telomeric quadruplex rearrangement, and the benefits of applying this approach to analyse other structures are discussed.